Use of Doppler ultrasonography for selection of recipients in embryo transfer programs in horses - Morelli, Karine Galhego (2023)
We aimed to evaluate the impact of corpus luteum (CL) and uterine characteristics accessed by B-mode and color Doppler ultrasonography in recipient mares at the time of embryo transfer (ET) on pregnancy outcomes. Recipient mares (n=110), between days 3 to 9 after spontaneous ovulation, received a fresh embryo. Immediately before ET, the reproductive system was assessed by transrectal palpation for the following parameters: uterine tone (0-3), CL echogenicity (0-6), CL type (homogeneous, trabecular or anechoic center), luteal area (cm2), uterine echogenicity (0-3), uterine edema (0-3), uterine echotexture (0-3), luteal blood perfusion (0-100%) and uterine blood perfusion (1-4). Additionally, a blood sample was collected by puncture of the jugular vein for plasma P4 dosage. Retrospectively, recipients were classified according to the luteal area (small [≤ 6 cm2] or large [> 6 cm2]), luteal blood perfusion (low [≤ 55%] or high [> 55%]), and plasma concentration of P4 (low ≤ 9.98 ng/mL or high > 9.98 ng/mL). Pregnancy diagnosis was performed at 15 and 30 days of gestation. Luteal blood perfusion was significantly higher (P= 0.03) in pregnant recipients (n= 83) than in non-pregnant recipients (n= 27). Overall P/ET was higher (P≤ 0.02) in mares with high luteal blood perfusion and high P4. Luteal blood perfusion was the most adequate significant (P= 0.01) predictor of pregnancy compared with the luteal area and plasma P4 concentration. Only luteal blood perfusion showed a linear (P= 0.03) and cubic (P= 0.004) effect on P/ET. In conclusion, CL blood perfusion determined by color-Doppler can be used in real-time to select recipients with the greatest chance of maintaining pregnancy in equine ET programs.